OPTIMIZATION OF OFFSHORE FLOATING SOLAR FARMS FOR MALAYSIAN OFFSHORE APPLICATIONS - Abdul Halim, Emiruddin Redza (IRC, 2019)
The burning of fossil fuels is considered responsible for the catastrophic climate changes, global warming, air pollution and energy insecurity. High emission of Greenhouse Gases such as Carbon Dioxide (CO2) and Nitrogen Oxide (NO2), has led towards an increase of awareness and demand for the application of renewable energy resources.